Uma palavra amarga: leitura do romance Vermelho Amargo pelo viés memorialístico - Souza, Bruno Henrique Muniz (2017)
This paper aims to analyze the novel Vermelho Amargo [Red Bitter], by Bartolomeu Campos de Queirós, from a memorialistic approach with a view of the formal composition of the narrative. Through the studies of Philippe Lejeune (2008) and Ecléa Bosi (1987) about both the shifting characteristics of the autobiographical genre and the perceptual act performed by the subject in his process of updating his past memories in the present of his enunciation, one can To infer that the writing of Queirós (2011) enacts not only a particular form of writing of the author, but also demands a specific way of reading on the part of its readers, in the search to understand this discourse full of meanings and traumas. From this perspective, the present study seeks to demonstrate how the story of this dazed narrator allows the observation of a deteriorated family relationship due to the absence of the mother and the traumatic arrival of his (narrator’s) stepmother. Thus, through complex textual strategies undertaken over the enunciative scenes of the novel, there are noted the multiple hues of a family portrait in ruins, metphorized in the numerous occurrences of the sign 'tomato', that are affecting this tormented subject by his memories until the end of his life.